Pendampingan Ibu Balita melalui Intervensi Responsive Feeding dalam Upaya Pencegahan Stunting - Erna Julianti; Adiyati Mardiyah; Zamziri Zamziri; Ummi Maktum (Universitas Baiturrahim, 2026)
Chronic nutritional problems in toddlers are caused by insufficient nutritional intake over a long period of time due to providing food that does not meet nutritional needs. Mothers play a role in feeding children, known as responsive feeding. Community Service Activities aim to improve the knowledge and practice of responsive feeding of toddler mothers before and after being given a responsive feeding intervention. This activity was carried out on August 15, 2025, in Labuh Air Pandan Village. Responsive feeding interventions include measuring body length/height, health education about responsive feeding, and demonstrations of making complementary foods. The implementation method was lectures, demonstrations, discussions, and questions and answers. The media used was PowerPoint. The results of the community service showed that the average knowledge of mothers after being given a responsive feeding intervention was higher at 81.3 compared to the average knowledge of mothers before being given a responsive feeding intervention of 54.20. In addition, there was an increase in responsive feeding practices before being given an intervention of 30% to 60% after being given a responsive feeding intervention, including the good category. Responsive feeding is important to be implemented by toddler mothers so that children's growth and development are optimal.